FRI0558 Further validation of the us7 score in a large cohort of patients with rheumatoid arthritis with different disease stages. (12th June 2018) - Podewski, A.F.; Glimm, A.-M.; Fischer, I.; Bruyn, G.A.W.; Burmester, G.-R.; Backhaus, M.; Ohrndorf, S.
Abstract : Background: Musculoskeletal ultrasound (US) is increasingly used in rheumatology clinical practice and research. Standardisation of US scanning techniques and definitions of pathologies is driven forward by the EULAR and OMERACT (Outcome measures in rheumatology) definitions and guidelines. However, no international consensus on a globally accepted US score system on patient level has been achieved so far. The US7 score, first published in 2009, assesses soft tissue lesions (synovitis, tenosynovitis/paratenonitis) as well as bone erosions of 7 preselected joints in one score. 1 Objectives: The aim of this retrospective analysis was to further validate the US7 score by a detailed analysis of affected joint regions in patients with different RA disease stages. Methods: The US7 score 1 examines the most commonly affected joints in RA, including the wrist, MCP2, 3, PIP2, 3 and MTP2, 5 joints, for synovitis and tenosynovitis/paratenonitis and bone erosions from dorsal, palmar, ulnar (wrist), radial (only MCP2) and lateral (only MTP5) by greyscale (GS) and power Doppler (PD) US. In this retrospective analysis, our population of 524 patients with RA was divided into 3 subgroups – 69 patients (13.2%) with very early RA (max. 6 months disease duration), 98 patients with early RA (>6 month, ≤2 years of disease duration), and 343 patients (65.5%) with established RA (>2 years disease duration). Patients were examined at baseline, 3, 6 and 12 months after starting or changing therapy (csDMARD/bDMARD). Results: MCP2 and the wrist (especially from dorsal) were most frequently affected by GS/PDUS synovitis in all groups. PDUS showed a slight tendency towards the dorsal versus the palmar joint side being more often affected in all groups. The group of established RA was more often affected by synovitis, while tenosynovitis/paratenonitis appeared more frequently in very early RA. Significant sensitivity to change within 12 months was detected by GSUS in the group of very early RA in all hand joint regions (for synovitis: p<0.001 MCP2, 3 and wrist; p=0.046 PIP2; p=0.001 PIP3) and MTP2 (p=0.024), but not in MTP5 (p=0.313). PDUS demonstrated that the palmar sides of MCP2, PIP2 (p<0.001 for all) as well as the dorsal sides of MCP2 (p=0.019), MCP3 (p=0.008), PIP2 and 3 (p=0.029 both), MTP5 (p=0.025) and all wrist sides (p<0.001, p=0.013, p=0.001, respectively) responded significantly to therapy, while MCP3, PIP3 palmar and MTP 2 dorsal did not show significant response (p=0054, p=0.494, p=0.172, respectively). In established RA, all joint regions included significantly responded to therapy (PIP2 GS: p=0.004, all others p≤0.001) in GS as well as PDUS. Conclusions: Based on these results, we recommend to include wrist and MCP2 joints in a global US score on the patient level to monitor RA, independent of the disease stage, since they are 1 most commonly affected by synovitis and 2 most responsive to therapy. Tenosynovitis/paratenonitis is frequent in very early RA and should therefore be implemented in an US score monitoring early disease stages. Reference: [1] Backhaus M, Ohrndorf S, Kellner H, Strunk J, Backhaus TM, Hartung W, et al. Evaluation of a novel 7-joint ultrasound score in daily rheumatologic practice: A pilot project. Arthritis Rheum2009;61(9):1194–201. Disclosure of Interest: None declared